Pengaruh Tingkat Pendidikan Dan Pengalaman Kerja Karyawan Terhadap Efektivitas Sistem Pengendalian Internal Pada KSP Kopdit Obor Mas Maumere - Mbeleng, Maria Margret; Mitan , Wilhelmina; Rangga, Yoseph Darius Purnama (Jurnal Projemen UNIPA, 2026)
The research was conducted at KSP Kopdit Obor Mas Maumere. The purpose of this study is to examine the effect of employees’education level and work experience on the effectiveness of the internal control system. The research method used is a quantitative approach with multiple linear regression analysis techniques. The research result show that the Education Level variable does not have a significant effect on the Effectiveness of the Internal Control System, while the Work Experience variable has a positive and significant effect on the Effectiveness of the Internal Control System. Simultaneously, both independent variables have a significant effect on the Effectiveness of the Internal Control System. The coefficient of determination (R2) indicates that variations in the effectiveness of the internal control system can be explained by Education Level and Work Experience. These findings affirm that Work Experience plays is dominant role in enhancing the effektiveness of the intenal control system, whereas Education Level is not a key factor in the context of this study.